In Vitro Activity of Sanfetrinem and Affinity for the Penicillin-Binding Proteins of Streptococcus pneumoniae - Sifaoui, Farid (American Society for Microbiology, 1998)
Against penicillin-susceptible pneumococci, the activity of sanfetrinem was similar to those of penicillin, amoxicillin, cefotaxime, imipenem, and meropenem, while against penicillin-resistant strains, sanfetrinem and the carbapenems exhibited superior activity (MICs at which 90% of strains are inhibited, ≤1 μg/ml). PBP 1a in the penicillin-susceptible strain and PBP 1a and PBP 2b in the more resistant isolates seemed to be the essential penicillin-binding proteins for imipenem and sanfetrinem.